Developments in the Financial Supply Chain and Its Impact on the Economy - Svetlana Sergeevna Meleschenko; Tatyana Anatolyevna Snetkova; Anna V. Lyzhova; Pavel Alexandrovich Aletkin; Sergey E. Markaryan (International Journal of Supply Chain Management, 2020)
Abstract— Although several studies have explored the relationship between the operation and performance of a supply chain (SC), a general SC model cannot deliver the expected financial results at a company-wide level. In this paper, we argue that this cannot guarantee the maximization of a firm’s overall value because short-term financial performance metrics do not reflect the risk to businesses and the invested capita. Information asymmetry determines investors to call for auditors’ services. Ensuring the reliability of compliance with the requirements of the financial reporting framework based on supply chain management is one of the fundamental factors for ensuring the quality of audit. This paper aims to analyze the influence of the financial reporting framework based on supply chain management on the process of forming the auditor's report. The process of developing financial statements is proceeding along the path of maximum informatization of these statements. Current users requirements are not always met by existing accounting and reporting standards. The capabilities inherent in the fair presentation framework push the boundaries of any standards, allowing the preparer to fill the financial statements with relevant information. Considering the financial statements framework on the part of the auditor, it can be argued that this will have an impact on the audit process. Objectively it consists in obtaining audit evidence and evaluating it. This means that the application of the fair presentation framework by the management of the audited entity will require the auditor to adjust the verification process accordingly, which should address such elements as the quality of audit evidence, the methods of obtaining it, and the auditor's assessment.